Rancang Bangun Aplikasi Pencatatan Aktivitas Guru Pada Sekolah Dasar Negeri Berbasis Web - Megawati Andi Safitri; Sulis Janu Hartati; Julianto Lemantara (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
The Problems in the research is how to recoprd and evaluation of teacher's activity as well as archiving the results from logging the activity of the teacher. With the process that is currently the principal felt less rapidly in the process of archiving and, therefore his headmaster wanted a recording of this activity online. The underlying principal to be made this teacher activity logging application online is that the principal did not experience difficulties in the process of evaluation and validation of the results of the logging activities of the teachers, so that principals can monitor the activity of the teachers not only in schools, but also who are outside the school.We based the development of systems that used the model of the waterfall. System development Model is a sequence of waterfall activities conducted in the development of systems ranging from identifying problems, analyzing and designing the system, build the system and test the system. Based on application trial results showed that this application can produce the recording activity of the teacher, and validation activities. The validation of the results of such activities can generate daily activity reports, monthly activity reports and quarterly activity reports of teachers. From the principal's report can see the graphic evaluation of the results of the logging activity reporting teacher. This application can be made online by going to www.kompetensi-gading1sby.com. Keywords: Recording, activity teachers, Waterfall, applications.